The presence of hydronephrosıs ın stagıng bladder cancer: an omınous sıgn - Köksal, Türker; Orhan, İrfan; Tefekli, Ahmet; Usta, Mustafa; Erdoğru, Tibet; Faruk Özcan (My University, 2000)
Objective: We investigated whether the presence of unilateral or bilateral upper tract obstruction could accurately predict advanced cancer stage. Methods: Six hundred and ten patients with bladder cancer entered into the tumor registries of our institutions between January 1990 and December 1994. The median patient age was 64 years (range 35 to 80). A total 75 (12%) patients had unilateral or bilateral hydronephrosis on an IVP at the time of initial diagnosis of the bladder cancer. Preoperative screening included physical examination, chest radiograph, complete blood count, blood urea nitrogen, creatinin, electrolyte analysis and IVP. Furthermore, patients were usually evaluated by bone scan and computerized tomography (CT). The diagnosis of transitional cell carcinoma was made by cystoscopy and transurethral resection of the tumor. Staging transurethral resection was done in all cases. Results: During a 5-year period 75 of 610 patients with carcinoma of the bladder had ureteral obstruction on excretory urography at the time of the initial diagnosis. Preoperative IVP revealed unilateral and bilateral hydronephrosis in 55 (73%) and 20 (27%) patients, respectively. Pathological staging revealed predominantly pT1 lesions for patients with unilateral obstruction. There were 30 (55%) patients with pT1, 10 (18%) with pT2, and 15 (27%) with pT3. Pathological staging revealed predominantly pT2 lesions for patients with bilateral obstruction. Pathological stage was pT2 in 10 (50%) cases, pT3 in 5 (25%), and pT4 in 5 (25%). Conclusion: IVP can be used in staging because hydronephrosis may Indicate the presence of a muscle-invasive bladder cancer, especially, bilateral hydronephrosis was strongly associated with advanced stage disease.
Keywords: Bladder cancer, excretory urography, clinical stage, pathological stage, transurethral resection.